Albania : From Isolation Toward Reform - Johnston, R. (Occasional Papers; Occasional Paper ;, 1992)
This study reviews Albania's historical and political background, as well as economic developments in 1991. It describes the centrally planned economic system up to the onset of reform and analyzes economic performance in the 1980s.